Empowering the Liberal Arts Student with Personal Flexibility for the World of Work - Crozier, Sharon D. (Canadian Journal of Counselling and Psychotherapy, 2011)
A series of six Career/Life Planning Modules was designed specifically to facilitate university students' concept of themselves as "active agents" in the career planning process. One of the workshops, in the series 'Translating a Degree into an Occupation", assists graduating Liberal Arts students to understand the unique skills and personal attributes they bring to the world of work. Assisting students to understand their potential in the world of work and how to manage their careers successfully is counselling for personal flexibility.